L’influence politique des églises évangéliques et la réaction conservatrice contre les politiques progressistes, sociales et écologiques en Colombie (2016-2024) - Sebastián Acevedo Ojeda (Revue Internationale des Études du Développement)
From the 1980s, the evangelical churches will take advantage of the progressive decline of Catholic influence to accelerate their expansion, gradually moving from an apolitical marginality to a desire to weigh in the political and social debates. Thus, they drive the reactionary movements, becoming allies of the extreme right and traditional Colombian rightists. These different evangelical currents will grow their social and political influence, reaching the benches of Congress and becoming major players in the backlash in Colombia. This article analyses the political power of evangelical movements which, through their communication strategies, impact on public policies and major debates in society, curbing progress on minority rights, and social and ecological initiatives.